Bycatch of northern fulmar (Fulmarus glacialis) in Norwegian longline fisheries: Assessing spatiotemporal variations in scale and risk to improve management - Clegg, Tom L.; Christensen-Dalsgaard, Signe; Bråthen, Vegard Sandøy; Tarroux, Arnaud; Danielsen, Johannis; Descamps, Sébastien; Follestad, Arne; Hallgrimsson, Gunnar Thor; Helberg, Morten; Helgason, Hálfdán H.; Jónsson, Jón Einar; Kolbeinsson, Yann; et al. (Global ecology and conservation, 2024)
Seabirds are vulnerable to bycatch in longline fisheries but for most species the impacts are largely unknown. To address this knowledge gap, studies can estimate bycatch directly using observations or calculate the theoretical risk of bycatch using overlap indexes. Here we quantify the scale and risk of bycatch of northern fulmar (Fulmarus glacialis) in the Norwegian offshore longline fishery using a ten-year time series of bycatch observations from a reference fleet programme, and large-scale datasets of fishing activity and northern fulmar distribution. We estimated an average of 0.01 (95 % CI: 0.008–0.03) northern fulmars bycaught per 1000 hooks, which results in a highly varying estimated annual bycatch of between 51 and 16242 (95 % CI) northern fulmars per year, with the largest hotspot in the Norwegian Sea during June-August. We compared these estimates with overlap indexes calculated for northern fulmars and the same fishing activity. This pinpointed the highest risk of bycatch within the breeding season, where fishing activity increased in the waters around the largest cluster of breeding colonies in the northeast Atlantic. Strong correlations between estimated bycatch and calculated overlap indexes validate overlap indexes as an indirect evaluation of risk and strengthen evidence for management decisions based on the spatial and temporal trends identified in our analyses.